PERANAN EPITELIAL TERHADAP EFEK RELAKSASI SENYAWA MARMIN DARI Aegle marmelos Correa PADA OTOT POLOS TRAKEA MARMUT TERISOLASI - , DADANG IRFAN HUSORI, Dr. Agung Endro Nugroho, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Marmin is a coumarin compound isolated from Aegle marmelos Correa. In the present study, we investigated the relaxation effect of marmin on guinea-pig isolated tracheal smooth muscle (TSM), and the role of epithelial on the effect. The study was conducted by using isolated-organ technique. The guinea- pig isolated TSM were incubated in organ bath containing Krebs solution and bubbled with a mixed gas of 95% O2 and 5% CO2. Removal of the tracheal epithelial was associated with significant increases in the potencies of histamine and metacholine to contract guinea-pig TSM. The pD2 value of histamine increased from 6.04±0.08 on intact trachea to 6.32±0.06 on epithelial-denuded trachea (p<0.05). The pD2 value of metacholine increased from 5.85±0.09 on intact trachea to 6.15±0.07 on epithelial-denuded trachea (p<0.05). Marmin showed relaxation effect on TSM induced by metacholine and histamine (3 x 10-5M). The relaxation effect of marmin is partially epithelial-dependent through the release of prostaglandin E2. However, nitric oxide, cGMP and β2-adrenergic-mediated relaxation contributed with a litle involvement.